Personal Branding in the Context of Generational Change - Pruchnik, Mateusz; Bryndza, Joanna (Personal branding w kontekście zmiany pokoleniowej, 2023)
Aim: This article aims to determine the importance of building a personal brand and to identify and characterize selected tools offered on the Internet that serve this process, with an emphasis on social media used by Generation Z. Methodology: The method of analysing the literature on the subject was used to achieve the assumed goal. Results: The research found that personal branding strategies require conscious image management to achieve authenticity and recognition among recipients. Implications and recommendations: The next stage will be survey research, analysing how Generation Z uses digital media to create its image, what strategies are most effective and what challenges they encounter. Originality/value: Personal branding is one of the most important intangible resources of an individual’s competitiveness, which concerns strategy and building a personal brand in the context of the development of social media and the Internet. Social media and websites have become key tools enabling individuals to build their identity and image in virtual space.
Business Informatics = Informatyka Ekonomiczna, 2023, Nr 1-2 (65-66), s. 42-50
Keywords: personal branding; social media; generation Z; media społecznościowe; pokolenie Z